Analysis of Real-Time Video for the Detection of Fire Using OpenCV - M. Gandhi, M. Gandhi; S. Manikandan, S. Manikandan; B. Vaidianathan, B. Vaidianathan (Research Parks Publishers, 2024)
Because of the wide range of colours and textures present in visual landscapes, fire detection is a challenging undertaking. To get over this issue, several fire image categorization methods have been suggested; nevertheless, the majority of these systems depend on rule-based methods or characteristics that are manually created. Develop and propose an innovative technique for fire picture detection using deep convolution neural networks. Adaptive piece-wise linear units are utilised in the network's hidden layers in place of conventional rectified linear units or tangent functions. In addition, we will generate a fresh, compact dataset of fire photos to use for model training and evaluation. Increasing the amount of training images available through the use of conventional data augmentation methods and generative adversarial networks helps alleviate the overfitting issue that arises from training the network on a small dataset. In this study, we compare and contrast two methods for measuring the geometrical features of wildland fires: one that uses image processing to identify colours, and the other that uses Mk2ethods. Presented here are two novel rules and two novel detection methods that make use of an intelligent combination of the rules; their respective performances are then evaluated. About 270 million non-fire pixels and 200 million fire pixels taken from 500 wild terrain photos taken under different imaging conditions are used to run the benchmark. Color and presence of fire are used to classify pixels as fire, whereas average intensity of the associated image is used to classify pixels as non-fire. Because of this, the future of Metrologic systems for detecting fires in unstructured environments looks bright thanks to this technology.